The impact of our past : a history of the United States - Weisberger, Bernard A. (St. Louis : Webster Division, McGraw-Hill, 1976)
A history of our country which may be used as a full-year course. Includes the Declaration of Independence, Constitution, and a list of Presidents.
Includes index.
Keywords: United States -- History